Towards a sociomaterial approach to inter-organizational boundaries: How information systems elicit relevant knowledge in government outsourcing. (June 2021) - Pelizza, Annalisa
This article furthers a sociomaterial framework to examine inter-organizational boundaries in government IT projects. It engages in a dialogue with the practice theory-based approach to boundary spanning and utilizes analytical tools and epistemologies drawn from the social studies of technology. It aims to contribute to a situated, material understanding of inter-organizational boundaries. We argue that boundaries in outsourcing relationships can be de facto enacted through definitions of what counts as relevant knowledge. Information systems have a key role in eliciting such definitions, thus establishing knowledge asymmetries and regimes of inclusion and exclusion. The article responds to the call to value the role of artefacts in IT research. Furthermore, it eventually shows that understanding knowledge asymmetries triggered at the micro-level of information systems can help to examine macro-scale transformations between the public and the private sectors. To illustrate the framework, two ethnographic case studies of governmental IT projects are discussed. The first case concerns a permit and licence submission service in Italy. The second case analyses a 20-year-long database integration carried on at the Dutch land registry. In the first case, information systems made relevant a form of knowledge developed by contractors; in the second case, the integration process valued knowledge developed in-house. Three sets of implications are drawn for the theory and practice of inter-organizational IT projects. To conclude, the article focuses on inter-organizational boundaries involving the public and the private sectors and foresees a novel interdisciplinary research direction at the confluence of information systems and political studies.